Simulasi Pemanfaatan Sistem Informasi Akuntansi Aksyaa.Com Berbasis Web dan Mobile Bagi UMKM - Wiriasto, Giri Wahyu; Misbahuddin, Misbahuddin; Iqbal, Muhamad Syamsu; Rachman, A. Sjamsjiar; Akbar, L. Syamsul Irfan (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Financial management has an important role in the success of micro, small and medium enterprises (MSMEs). MSME owners face challenges when improving their business performance due to difficulties in managing their financial resources effectively. One of the factors contributing to this challenge is the mix of their business and personal operating funds. Because of this, a free licensed financial management system start-up called aksyaa.com was developed. Aksyaa.com has features for recording general journals, reporting sales and purchases, and ledgers. Output documents include sales reports, purchases, cash flow statements, balance sheets, and income statements. Aksyaa.com on a web and android basis has been selectively implemented and simulated for several MSMEs as part of community service activities from the Faculty of Engineering, University of Mataram. One of the user partners, MSMEs engaged in selling furniture products in the city of Mataram, managed to use the system by inputting transaction data, so that there were 798 transactions recorded within one month. Output documents are consistently aligned with the list of accounts provided in the system, categorized by transaction type, and when testing the system no bugs were detected.